A multimodal framework using audio, visible and infrared imagery for surveillance and security applications. (29th June 2009) - Kumar, Praveen; Mittal, Ankush; Kumar, Padam
This paper presents a low-cost framework for combining multimodal information (visible, IR and audio signal) for small area surveillance and security applications. The system uses audio and video information to capture different aspects of the environment and infrared imagery is used for low lighting conditions. The visual processing module of the system uses a motion-based approach for detecting objects, and Kalman filter for tracking. Environmental sound is recognised by extracting Mel-Frequency Cepstral Coefficients (MLCCs) audio features and then classified by Dynamic Time Warping (DTW) technique. Experimental results on some typical sequences show promising results.